Women, donors and land administration: The Tanzania case - Rasmus Hundsbæk Pedersen; Scholastica Haule (Danish Institute for International Studies (DIIS), 2013)
Tanzania's land reform from 1999 has been evaluated as among the most gender-sensitive of its kind in Sub-Saharan Africa. However, there is a gap between the legal framework and what is happening on the ground. This working paper analyses the challenges related to the protection of women's rights to land in rural areas. It provides detailed information on reform implementation experiences so far by analysing a number of government and NGO interventions. It furthermore discusses the ambiguous role of donors. The paper makes it clear that the fight for women's rights has not been won just because the legal framework is right. Discriminatory practices persist at formal as well as at customary institutions, disadvantaging women's access to land. Women's rights should therefore be mainstreamed into every activity that relates to land, land administration and land dispute settlement, from policy formulation over implementation to evaluation.
Keywords: 300